Encapsulated human islets in alginate fiber maintain long-term functionality - Junko Nishida; Takahiro Tsuno; Shigeharu G. Yabe; Tatsuya Kin; Satsuki Fukuda; Fujie Takeda; Jun Shirakawa; Hitoshi Okochi (Endocrine Journal)
Maintenance of islet function after in vitro culture is crucial for both transplantation and research. Here we evaluated the effects of encapsulation in alginate fiber on the function of human islets which were distributed by the Alberta Islet Distribution Program. Encapsulated human islets from 15 deceased donors were cultured under 5.5 or 25 mM glucose conditions in vitro. The amounts of C-peptide and glucagon secreted from encapsulated islets into the culture media were measured periodically, and immunohistochemical studies were performed. Encapsulated islets maintained C-peptide and glucagon secretion for more than 75 days in 5 cases; in two cases, their secretion was also successfully detected even on day 180. α- and β-cell composition and β-cell survival in islets were unaltered in the fiber after 75 or 180 days of culture. The encapsulated islets cultured with 5.5 mM glucose, but not those with 25 mM glucose, exhibited glucose responsiveness of C-peptide secretion until day 180. We demonstrate that alginate encapsulation enabled human islets to maintain their viability and glucose responsiveness of C-peptide secretion after long-term in vitro culture, potentially for more than for 180 days.